Exploring Motivation and Challenges: Online Professional Teacher Education (PPG) for Pre-Elderly Students in Indonesia - Karnadi, Karnadi; Istiyani, Dwi (International Journal of Social Learning (IJSL), 2024)
Limited technological mastery challenges pre-elderly students participating in online Teacher Professional Education (PPG) programs. This study explores their motivation and obstacles through a mixed research approach. Four key motivational factors were identified: intrinsic, career, social, and economic. These factors drive their decision to pursue further education in teaching. However, technological and digital skill limitations remain significant barriers. Institutional support addresses these challenges such as specialized digital training and mentoring. Such initiatives help students critically reflect on their limitations and shift their perspectives on online learning. Aligning with Jack Mezirow's transformative learning theory, this process emphasizes critical reflection to overcome obstacles and foster perspective changes. Ultimately, this approach enables pre-elderly students to effectively achieve their learning goals, enhancing their contributions to academic and professional communities.